Family Communication Model in Forming Pious Children - Yan Hendra; Ribut Priadi (Budapest International Research and Critics University, 2019)
Piousness children can not be separated from the communication built by parents in the family. Through this research a search for family communication was carried out so as to form a pious child. The research problem is, what is the model of family communication in sholeh children. The study uses a qualitative approach with qualitative descriptive methods. Research data is obtained through interviewing parents of pious children. The results showes that the family communication model in forming pious children was built by four foundations, namely the intensity of family communication consisting of frequency and duration of communication, family communication patterns consisting of atmosphere, communication and flow of communication, communication methods that tended to be persuasive and coercive, methods planting of value values consisting of exemplary methods, habituation, discipline, enforcement of rules that must be obeyed by children.